2019
DOI: 10.1101/802504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short interval intracortical inhibition as measured by TMS-EEG

Abstract: The diagnosis of amyotrophic lateral sclerosis (ALS) relies on involvement of both upper (UMN) lower motor neurons (LMN). Yet, there remains no objective marker of UMN involvement, limiting early diagnosis of ALS. This study establishes whether TMS combined with EEG can be used to measure short-interval intracortical inhibition (SICI) via TMS evoked potentials (TEP) in healthy volunteers -an essential first step in developing an independent marker of UMN involvement in ALS.We hypothesised that a SICI paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…SICI refers to the reduction in MEP amplitude to a TMS pulse that is preceded 1-5ms by a subthreshold pulse, due to activation of GABA A receptors (Kujirai et al, 1993). Some studies have reported associations between SICI and the TEP N45 (Leodori et al, 2019;Rawji, Kaczmarczyk, Rocchi, Rothwell, & Sharma, 2019), suggesting the two may share common neurophysiological mechanisms. However, we also found that a larger reduction in MEP amplitude during pain was associated with less pain, while a larger increase in N45 peak during pain was associated with stronger pain ratings, suggesting that inhibitory processes mediating corticomotor excitability and the N45 peak during pain are distinct.…”
Section: The Tep Vs Mep Response To Painmentioning
confidence: 99%
“…SICI refers to the reduction in MEP amplitude to a TMS pulse that is preceded 1-5ms by a subthreshold pulse, due to activation of GABA A receptors (Kujirai et al, 1993). Some studies have reported associations between SICI and the TEP N45 (Leodori et al, 2019;Rawji, Kaczmarczyk, Rocchi, Rothwell, & Sharma, 2019), suggesting the two may share common neurophysiological mechanisms. However, we also found that a larger reduction in MEP amplitude during pain was associated with less pain, while a larger increase in N45 peak during pain was associated with stronger pain ratings, suggesting that inhibitory processes mediating corticomotor excitability and the N45 peak during pain are distinct.…”
Section: The Tep Vs Mep Response To Painmentioning
confidence: 99%
“…Particularly in patients with brain tumors, the rMT can be frequently high in the tumor-affected hemisphere, and accurate mapping with a lower SI related to a lower determined rMT could permit successful use of nTMS even in the most demanding cases. This may also be highly relevant for other applications of nTMS in patients with brain tumors, such as language mapping [197][198][199][200][201]. In such applications, a higher SI is often used and stimulation is more widespread and, thus, can entail discomfort that negatively interferes with the mapping outcome.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…For instance, the information given by TEPs obtained from M1 TMS may not completely overlap with those provided by MEPs; indeed, the latter arise from excitation of PTN and associated circuitry, whereas the former probably reflect activity of a larger ensemble of cortical cells [89,100,195]. Therefore, caution should be used when comparing conclusions drawn by the two variables, especially for ppTMS protocols, which were devised for MEPs, and are still of uncertain interpretation in the TMS-EEG setting [112,196,197]. Another issue is related to the use of TEPs to measure brain connectivity.…”
Section: Abbreviationsmentioning
confidence: 99%
“…For instance, the information given by TEPs obtained from M1 TMS may not completely overlap with those provided by MEPs; indeed, the latter arise from excitation of PTN and associated circuitry, whereas the former probably reflect activity of a larger ensemble of cortical cells [ 89 , 100 , 195 ]. Therefore, caution should be used when comparing conclusions drawn by the two variables, especially for ppTMS protocols, which were devised for MEPs, and are still of uncertain interpretation in the TMS-EEG setting [ 112 , 196 , 197 ]. Another issue is related to the use of TEPs to measure brain connectivity.…”
Section: Limitations Perspectives and Conclusionmentioning
confidence: 99%